IMPLEMENTASI SUPERVISI OLEH PENGAWAS SEKOLAH TERHADAP PENINGKATAN KETERAMPILAN GURU DALAM PROSES BELAJAR MENGAJAR - Salfilla Juliana (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This research was motivated by the weakness of teachers in carrying out the learning process in Bandar Laksamana 1 Public Middle School. The purpose of this study is to improve the skills of teachers teaching in the classroom with the help of supervision. This research was conducted at Bandar Laksamana 1 Public Middle School. This research is a classroom action research consisting of two cycles with. Each cycle consists of four stages such as planning, implementation, observation, and reflection. The results of the study show that on the basic score, teacher teaching skills are included in the sufficient category with an average score of 60.21. After improvements were made in the first cycle, the results of the teacher's skills assessment increased to a good category with the teacher's average score of 75.54. For the implementation of the teacher's skills assessment in teaching in the second cycle again increased with a very good category with an average value of 85.75. Based on the results of the above research, researchers can conclude that with the implementation of supervision in Bandar Laksamana 1 Junior High School can improve teacher skills in teaching.